Physical Activity and Health Promotion in Esports and Gaming–Discussing Unique Opportunities for an Unprecedented Cultural Phenomenon - Ketelhut, Sascha; Martin-Niedecken, Anna Lisa; Zimmermann, Patrick; Nigg, Claudio R. (Frontiers in Sports and Active Living, 2021)
Due to long periods of sedentary behavior, and unhealthy diets gamers and esports players are at risk for numerous chronic diseases and all-cause mortality. Health research has started addressing the public health implications of the esports phenomenon, drawing a bleak picture of this megatrend. However, instead of just highlighting adverse public health implications of this trend, it is recommended to become involved in this phenomenon and positively influence it. Esports has an enormous potential for physical activity and health-promoting efforts, provides a context for broadly disseminating interventions, and offers new ways of gaining access to an often-neglected population. This paper presents: the potential of the esports phenomenon to promote physical activity, health, and well-being in gamers and esports players; the strategic and preventive solutions to ameliorate esports possible adverse health impacts; and the utilization of esports technology (streams, media platforms, exergames, etc.) as an innovative health promotion tool, especially reaching gamers and esports players with attractive and interactive interventions. This is to encourage systematic scientific research so that evidence-based guidelines and intervention strategies involving regular physical activity, healthy diet, and sleep hygiene for esports will be developed. The goal is to promote public health approaches that move toward a better integration of esports and gaming.